Anti-Inflammatory Properties of Dendrimers per se - Myriam Hayder; Séverine Fruchon; Jean-Jacques Fournié; Mary Poupot; Rémy Poupot (The Scientific World Journal)
Dendrimers are polybranched and polyfunctionalized tree-like polymers. Unlike linear polymers, they have perfectly defined structure and molecular weight, due to their iterative step-by-step synthesis. Their multivalent structure and supramolecular properties have made them attractive nanotools for applications, particularly in biology and medicine. Among the different biological and medical properties of dendrimers that have been developed over the past decades, the anti-inflammatory properties of several groups of dendrimers are the most recently discovered. Thereof, dendrimers emerge as promising, although heretical, drug candidates for the treatment of still-uncured chronic inflammatory disorders. This mini-review is based on the five main scientific articles giving an overview of what can be the spectrum of anti-inflammatory characteristics displayed by dendrimers.